Calculating System for Poor Student Assistance (BSM) Using the MFEP (Multi Factor Evaluation Process): Calculating System for Poor Student Assistance (BSM) Using the MFEP (Multi Factor Evaluation Process) - Rani Purnama (Adpebi Science Series, 2022)
SMA Negeri 2 MuaraBeliti was a secondary school establishment that was occupied with understudy undertakings and gives a few grants, one of which is a grant program for the oppressed by using the SIC (Smart Indonesian Card). Up to this point, the understudy office has experienced issues in deciding understudies who were qualified for grants and appears to be abstract in its appraisal disregarding different prerequisites, bringing about disparity in the granting of grants. The motivation behind this exploration is to assemble a choice emotionally supportive network by utilizing the Multi Factor Evaluation Process technique to help the most common way of computing possibility for getting help for helpless understudies. the Multi Factor Evaluation Process technique which has measures like KIP, Student Values, Parental Income, Parental Ownership, Personality, and Dependents. Old. The consequence of this exploration was making by this framework, it can help the appraisal group figure out which understudies were qualified to get the Poor Student Assistance (BSM) as per the rules set.